2004
DOI: 10.1182/blood-2003-09-3192
|View full text |Cite
|
Sign up to set email alerts
|

Engraftment of NOD/SCID-β2 microglobulin null mice with multilineage neoplastic cells from patients with myelodysplastic syndrome

Abstract: The development of immunodeficient mouse xenograft models has greatly facilitated the investigation of some human hematopoietic malignancies, but application of this approach to the myelodysplastic syndromes (MDSs) has proven difficult. We now show that cells from most MDS patients (including all subtypes) repopulate nonobese diabetic-severe combined immunodeficient (scid)/scid-␤2 microglobulin null (NOD/SCID-␤2m ؊/؊ ) mice at least transiently and produce abnormal differentiation patterns in this model. Norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
2
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 60 publications
4
72
2
4
Order By: Relevance
“…82 In another study, the results of MDS sample engraftment suggested the presence of a relatively late type of 'multilineage but myeloid-restricted' neoplastic 'stem' cell with repopulating activity, limited self-renewal ability, and skewed differentiation potential. 83 These findings also show that the repopulating cells present in MDS patients include residual normal or pre-neoplastic repopulating cells with normal features that outcompete the neoplastic clone if adequately stimulated. Recently, a transgenic approach has provided evidence that disturbance of the endosteal niche can result in MDS.…”
Section: 79mentioning
confidence: 66%
“…82 In another study, the results of MDS sample engraftment suggested the presence of a relatively late type of 'multilineage but myeloid-restricted' neoplastic 'stem' cell with repopulating activity, limited self-renewal ability, and skewed differentiation potential. 83 These findings also show that the repopulating cells present in MDS patients include residual normal or pre-neoplastic repopulating cells with normal features that outcompete the neoplastic clone if adequately stimulated. Recently, a transgenic approach has provided evidence that disturbance of the endosteal niche can result in MDS.…”
Section: 79mentioning
confidence: 66%
“…In a modified study, modest engraftment (Ͻ5%) of cells with clonal markers characteristic of the MDS clone was detected 13-17 weeks after intramedullary transplant of cells into NOD/SCID/␤2 microglobulin (NOD/SCID-␤2m null ) mice (15). Investigators using NOD/SCID-␤2m null mice that were engineered to express human IL3, granulocyte-macrophage colony-stimulating factor (GM-CSF), and Steel Factor (SF) demonstrated that BM cells from 9 of 11 MDS patients generated detectable levels of human hematopoietic cells (14). However, engraftment was transient in some cases, clonal markers indicated that 15-99% of the cells were derived from normal hematopoietic cells, and there was no evidence that the mice developed peripheral blood cytopenias or other evidence of clinical MDS.…”
Section: Discussionmentioning
confidence: 99%
“…Although MDS has been recognized as a disease entity for 50 years (13) and is considered to be a clonal stem cell disorder, efforts to verify this hypothesis using xenograft mouse transplantation models have failed, because the MDS cells either engraft poorly or not at all (14)(15)(16), and the mice do not develop clinical evidence of MDS. These results stand in contrast to those obtained with AML, in which the disease can be readily transplanted into immunodeficient mice (17); these xenotransplant assays have been crucial for the identification of a subset of cells that can transfer leukemia to immunodeficient recipients; referred to as leukemia-initiating cells (L-ICs) (17,18).…”
mentioning
confidence: 99%
“…Involvement of non-myeloid lineages is controversial as some research report MDS associated chromosome abnormalities in T-cell, B-cell, or natural killer-cell populations while some other reports claim for the absence of such chromosome aberrations in lymphoid lineages [40,41]. While MDS has very rare chance of evolving into lymphoid acute leukemia, it is noteworthy to indicate that as most of the research have proven; the dysplasia and aberrations are more prominent in cells committed to myeloid lineages [42]. However, some reports argue that only del 5q could be seen at more primitive HSCs and other aberrations like trisomy 8 might occur at later stages in the hematopoietic hierarchy [40,43].…”
Section: The Occurrence Of Cytogenetic Abnormalities In Mdshscsmentioning
confidence: 99%
“…The common recurring cytogenetic abnormalities in MDS include del(5q), -7/del(7q), -8,-18/del (18q), del (20q),-5,-Y,-17/del (17p) including isochromosome (17q), -21, inv/t(3q), -13/del (13q), -1/del (1q), -21, -11, del (12p), t(5q), del (11q), and t(7q) [1,2,[35][36][37][38][39][40][41][42][43]. The initiator hematopoietic cell with cytogenetic abnormalities in the hierarchy of hematopoiesis is yet to be identified.…”
Section: The Occurrence Of Cytogenetic Abnormalities In Mdshscsmentioning
confidence: 99%